Gender Construction and Diversity in Icelandic Fishing Communities - Skaptadóttir, Unnur Dís (Anthropologica, 2022)
This article combines an analysis of the social construction of gender inequality with an examination of the construction of other kinds of diversity among women in small fishing villages in Iceland. This combination is necessary in order to avoid the creation of a static categorization of women in the fisheries. The construction of commonalities and diversities among women and between women and men is examined. Gender and diversity are generated locally, and in relation to the larger world. Women have a common identity as inhabitants of small fishing villages, an important identity they share with men to some extent. However, among them there are important dissimilarities based on many factors, including, for example, the different relations to the fisheries experienced by fishermen's wives and fish processors.